PENINJAUAN PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT ADHI COMMUTER PROPERTY CISAUK POINT - Yunita Purnama Sari; Abdul Azis (Jurnal Menara, 2026)
This study aims to examine the influence of career development and motivation on employee performance at PT Adhi Commuter Property Cisauk Point. The research method used is quantitative, with a population of 53 employees. The data analysis techniques applied include validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t-test, and F-test.The results of the analysis show that the multiple regression equation is Y = 3.964 + 0.368 X1 + 0.546 X2. The correlation coefficient between career development and motivation variables is 0.948, indicating a very strong relationship. The coefficient of determination is 0.898, meaning that career development and motivation influence employee performance by 89.8%, while the remaining 10.2% is affected by other factors.Based on the t-test hypothesis, the career development variable has a t-value of 2.780 ≥ t-table 2.00758 and a significance level of 0.008 ≤ 0.05. The motivation variable has a t-value of 3.985 ≥ t-table 2.00758 and a significance level of 0.001 ≤ 0.05. This indicates that both career development and motivation have a positive and significant partial effect on employee performance.The F-test results show an F-value of 220.048 ≥ F-table 3.183 and a significance level of 0.001 ≤ 0.05, which means that career development and motivation simultaneously have a positive and significant effect on employee performance